A hospital based cross sectional study of clinical picture and spirometry pattern on interstitial lung diseases at a tertiary care centre - Lal, Roshan; Kumar, Pratik (International Journal of Advances in Medicine, 2019)
Background: Many of the ILDs are difficult to differentiate on clinical examination and history as they have similar clinical features. Symptom complex is not beyond that of respiratory symptoms. The objective was to study the clinical picture and spirometry pattern of the patients having interstitial lung disease. Methods: Hospital based cross sectional study was carried out among 73 cases of ILDs. Data related to history, clinical examination was recorded. Six minute walk test and spirometry was carried out. The data was analysed using proportions. Results: Incidence of Idiopathic pulmonary fibrosis (IPF) increased with age. Exertional dyspnea (100%) and cough (95.9%) were the commonest presenting symptoms amongst ILD patients. End inspiratory fine crackles (95.1%) and clubbing (67.1%) are the predominant clinical signs. Mean BMI of various ILDs patients were 24.86±8.2 Kg/m² in NSIP followed by 22.9±4.6 in sarcoidosis 21.9±6.4 and 20.8±3.94 in IPF and in Cryptogenic Organizing Pneumonias 19.34±1.8 Kg/M². Serum ACE level was raised in 69.2% patients of sarcoidosis. 81 % of patients could successfully perform 6 Minute Walk Test. Among those who could perform, average desaturation was 8.11% in sarcoidosis, 7.52% in IPF, 6.0% In Hypersensitivity Pneumonitis, 5.75% in NSIP and 4.75% in CTD associated ILDs patients. Raised C Reactive Protein label was consistent (45.2%) in ILDs, maximum in HP (63%) and 2 out of 3 patients with COP and 3 out of 5 patients of CTD associated ILDs. 17.8% cases had positive serum ANA, maximum in IPF. Conclusions: Idiopathic pulmonary fibrosis (IPF) was the commonest Interstitial Lung disease present in 39.7% of 73 cases followed by sarcoidosis in 17.9%, cases.